2010
DOI: 10.1152/ajpcell.00373.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium-dependent sodium uptake in mitochondrion-rich cells of medaka (Oryzias latipes) larvae

Abstract: LY. Ammonium-dependent sodium uptake in mitochondrion-rich cells of medaka (Oryzias latipes) larvae. In this study, a scanning ion-selective electrode technique (SIET) was applied to measure H ϩ , Na ϩ , and NH 4 ϩ gradients and apparent fluxes at specific cells on the skin of medaka larvae. Na ϩ uptake and NH3/NH 4 ϩ excretion were detected at most mitochondrion-rich cells (MRCs). H ϩ probing at MRCs revealed two group of MRCs, i.e., acid-secreting and base-secreting MRCs. Treatment with EIPA (100 M) blocked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
155
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(173 citation statements)
references
References 51 publications
13
155
5
Order By: Relevance
“…8a). Location of NKA gene and protein expression matched with previous reports (Thermes et al 2010, Wu et al 2010). All treatments except Cit-TA24 led to significant increase in number of NKA expressing cells relative to control as indicated by Dunnett's test following one-way ANOVA (Fig.…”
Section: Localization Of Na + /K + Atpase Expression and Translationsupporting
confidence: 82%
See 1 more Smart Citation
“…8a). Location of NKA gene and protein expression matched with previous reports (Thermes et al 2010, Wu et al 2010). All treatments except Cit-TA24 led to significant increase in number of NKA expressing cells relative to control as indicated by Dunnett's test following one-way ANOVA (Fig.…”
Section: Localization Of Na + /K + Atpase Expression and Translationsupporting
confidence: 82%
“…This antibody can specifically label NKA protein expressing cells in medaka larvae (Wu et al 2010). After rinsing with PBS for 20 min, samples were further incubated in anti-mouse IgG antibody (1:200 dilution) for 2h at room temperature.…”
Section: Whole Mount In Situ Hybridization and Immunohistochemistry Dmentioning
confidence: 99%
“…In the mangrove killifish, which volatilises ammonia through the skin, Rh mRNA levels were upregulated in the skin after HEA and also aerial exposure . The most convincing evidence of Rh involvement in skin ammonia excretion, however, was provided by Shih et al (Shih et al, 2008) in zebrafish larvae and by Wu et al (Wu et al, 2010) in medaka larvae, both of whom demonstrated, using the scanning ion electrode technique, that Rhcg1 facilitated ammonia excretion across MRC-type cells in the skin. In the present study, exposure of pufferfish to 1mmoll -1 NH 4 HCO 3 for 48h did not result in significant changes of skin Rh mRNA levels (Fig.5); however, exposure to 5mmoll -1 NH 4 HCO 3 resulted in an upregulation of both Rhbg and Rhcg2 mRNA (Table2).…”
Section: A Role For the Skin?mentioning
confidence: 99%
“…However, similar in vivo inhibitor studies in loach with 10 glycoprotein ammonia transporters facilitate branchial ammonia excretion (Weihrauch et al, 2009;Wright and Wood, 2009). However, recent studies in the yolk sac skin (surrogate gill ionocyte model) of larval fish give the best detailed mechanistic evidence of the role of the NHE in ammonia excretion (Shih et al, 2008;Shih et al, 2012;Wu et al, 2010;Kumai and Perry, 2011). In zebrafish larvae skin, although the H + -ATPase still dominates the proton flux (80%) (Shih et al, 2008), NHE3b gene knockdown and EIPA have also been shown to decrease the proton gradient that drives facilitated NH 3 diffusion by an acid-trapping mechanism through the apical Rh glycoprotein ammonia transporter Rhcg1 under low sodium (Shih et al, 2012) and low pH (Kumai and Perry, 2011) conditions when NHE3b expression is enhanced.…”
Section: Gut Membrane Fluiditymentioning
confidence: 99%